"Nine years in Egypt": Al-Azhar University and the Arabization of Chinese Islam - Benite, Zvi Ben-Dor (Hagar: Studies in Society and Culture, 2008)
This essay presents and discusses aspects and notions of exile and exilic world view in Chinese Islam. This exilic world view emerged in early modern times in response to removal from the Muslim world and Islamic history. The paper discusses the transformation of this world view during die early twentieth century, a time when China integrated rapidly with global transportation and communication networks. I argue that the reintegration of Chinese Islam with the Muslim world gave rise, among other things, to a process of "Arabization" as a means to "return" to their original state before being "exiled" in China. In this regard, I contend that integration with the Islamic world did not simply remove the sense of exile among Chinese Muslims; rather, the sense of exile informed and shaped the ways in which Chinese Muslims understood the integration itself.